2010
DOI: 10.5016/1980-6574.2010v16n4p869
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da estimulação cortical na variável tempo de reação e performance hábil-motriz-cognitiva em jovens atletas de futebol

Abstract: O Ser humano possui grande poder de adaptação em sofrer mudanças em qualquer meio, usando para isso comandos através do cérebro sendo um sistema aberto de grande plasticidade que são alterados ao longo de nosso desenvolvimento, tendo uma enorme capacidade de aprendizagem e transformação de acordo com as mudanças ocorridas com o nosso processo evolutivo, onde existem diversos estudos comprovando a influencia da estimulação cortical para aprendizagem hábil-motriz e cognitiva. Sabe-se que uma das particularidades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In the same sense, Ribeiro Júnior et al [ 1 ] observed the effect of photic and auditory stimulation in the variable reaction time and skilled motor-cognitive efficiency of 20 football players. The athletes were divided into two groups of 10 individuals that performed a task: kicking a ball in a specific quadrant marked in the goal area in response to a random light stimulus.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…In the same sense, Ribeiro Júnior et al [ 1 ] observed the effect of photic and auditory stimulation in the variable reaction time and skilled motor-cognitive efficiency of 20 football players. The athletes were divided into two groups of 10 individuals that performed a task: kicking a ball in a specific quadrant marked in the goal area in response to a random light stimulus.…”
Section: Resultsmentioning
confidence: 88%
“…Still in the sports context, Ribeiro Júnior et al [ 1 ] sought to determine the effect of photic and auditory stimulation in the variable reaction time and skilled cognitive-motor efficiency in soccer players. The adopted procedure produced in the players of experimental group a statistically significant improvement in the motor performance and consequently in the mental processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations